2021
DOI: 10.1002/ese3.1037
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of longwall mining‐induced stress in roof rock using LSTM neural network and transfer learning method

Abstract: Rock bursts are a common dynamic disaster in coal mines, and they crucially affect the safety, economics, and efficiency of mining operations. The mitigation and control of rock bursts is challenging owing to their violent, unpredictable characteristics. 1,2 Rock bursts are characterized by the sudden release of elastic strain energy in rock and coal during mining or roadway excavation. The mining-induced redistributed high-stress regions around surrounding rocks are crucial for the evaluation of rock bursts r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The latter is induced by roadway excavation and timely variations. The measurement method for the in situ stress was introduced in our previous study, 33 based on which the in situ stress for the study case is listed in Table 3, where the compressive stress is negative and the tensile stress is positive. The developed stress sensor was then used to monitor the variation in mining-induced stress, and the monitoring results are shown in Figure 8.…”
Section: Background For a Study Casementioning
confidence: 99%
“…The latter is induced by roadway excavation and timely variations. The measurement method for the in situ stress was introduced in our previous study, 33 based on which the in situ stress for the study case is listed in Table 3, where the compressive stress is negative and the tensile stress is positive. The developed stress sensor was then used to monitor the variation in mining-induced stress, and the monitoring results are shown in Figure 8.…”
Section: Background For a Study Casementioning
confidence: 99%
“…In recent years, with the rapid advancement of artificial intelligence and big data technologies, machine learning methods have gained increasing attention and application in the realm of lateral spreading prediction research. Among these methods, algorithms based on machine learning have shown tremendous potential for developing data-driven predictive models [10], [11]. Traditional analytical approaches often require precise function relationships, yet complex seismic phenomena like liquefaction-induced lateral spreading are often challenging to accurately describe using simple mathematical models.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the maximum stress decreased with increasing temperature, and it increased with an increasing strain rate. These people established the constitutive models required for quantitative analysis based on experimental samples, but these have rarely been combined with CT experiments [9,[12][13][14][15][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%